Functional domains of the granulocyte colony-stimulating factor receptor. - Fukunaga, R (1991)
The granulocyte colony-stimulating factor (G-CSF) receptor has a composite structure consisting of an immunoglobulin(Ig)-like domain, a cytokine receptor-homologous (CRH) domain and three fibronectin type III (FNIII) domains in the extracellular region. Introduction of G-CSF receptor cDNA into IL-3-dependent murine myeloid cell line FDC-P1 and pro-B cell line BAF-B03, which normally do not respond to G-CSF, enabled them to proliferate in response to G-CSF. On the other hand, expression of the G-CSF receptor cDNA in the IL-2-dependent T cell line CTLL-2 did not enable it to grow in response to G-CSF, although G-CSF could transiently stimulate DNA synthesis. Mutational analyses of the G-CSF receptor in FDC-P1 cells indicated that the N-terminal half of the CRH domain was essential for the recognition of G-CSF, but the Ig-like, FNIII and cytoplasmic domains were not. The CRH domain and a portion of the cytoplasmic domain of about 100 amino acids in length were indispensable for transduction of the G-CSF-triggered growth signal.